1995
DOI: 10.1103/physrevb.52.850
|View full text |Cite
|
Sign up to set email alerts
|

Ion implantation in tetrahedral amorphous carbon

Abstract: Tetrahedral amorphous carbon (ta-C) is a dense form of amorphous carbon with a structure consisting of a highly tetrahedral bonding network. Approximately 20% of the atoms in ta-C are sp hybridized and the presence of these sites plays an important role in the electrical and optical properties of the material. In the present investigation, we use 50 keV C+ and 200 keV Xe+ ion implantation to damage the structure in a controlled manner. The structure of the ta-C following ion irradiation is monitored using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 27 publications
4
48
0
Order By: Relevance
“…5͒ in the transition region, the peak at k = 1.77 Å −1 indicates the presence of material with sp 2 bonding and the peak at k = 2.8 Å −1 in the same diffraction pattern indicates the presence of ta-C. An almost identical diffraction pattern has been observed previously in ion implanted ta-C in which the microstructure was found to be a mixture of ta-C and sp 2 -rich a-C clusters created by ion beam damage. 18 It is conceivable that this type of microstructure may be present in the films in the transition region of this study. Films prepared within the transition region at high energies ͑see the sample prepared at 420 eV in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…5͒ in the transition region, the peak at k = 1.77 Å −1 indicates the presence of material with sp 2 bonding and the peak at k = 2.8 Å −1 in the same diffraction pattern indicates the presence of ta-C. An almost identical diffraction pattern has been observed previously in ion implanted ta-C in which the microstructure was found to be a mixture of ta-C and sp 2 -rich a-C clusters created by ion beam damage. 18 It is conceivable that this type of microstructure may be present in the films in the transition region of this study. Films prepared within the transition region at high energies ͑see the sample prepared at 420 eV in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Reductions in film resistivity with concomitant falls in the optical band gap as a function of ion dose were reported in ta-C by McCulloch et al, 13 and in diamondlike a-C:H by Prawer et al 14 In the former, the reduction of the optical gap and the decrease in film resistivity occurred even at the lowest doses investigated (10 13 cm Ϫ2 ), and appeared to be concomitant. In the latter study, the resistivity remained constant up to a dose of 10 15 cm Ϫ2 and then decreased, and the optical gap decreased from about 1.5 eV in the as-grown film to less than 1 eV (2ϫ10 17 cm Ϫ2 ), following the variation in the resistivity.…”
Section: Rapid Communicationsmentioning
confidence: 91%
“…An alternative approach is to perform localized heating by means of ion implantation, whereby it is possible to deposit highly localized energy in a controlled manner. Previous studies of damage as a result of ion implantation found extensive sp 2 restructuring ͑graphiti-zation͒ at very high doses, 13,14 and a consequent increase in film conductivity. However, by controlling the ion dose we show that it is possible to enhance the conductivity through the film, but prevent macroscopic graphitization.…”
mentioning
confidence: 99%
“…EELS analysis of a highly graphitic ultramicrotomed glassy carbon specimen was also conducted to provide a spectral reference of a solid containing practically complete sp 2 bonding [6]. As a consistency check, EELS data of one of the specimen was also collected using a high-resolution Scanning TEM (VGSTEM HB601) equipped with an Enfina spectrometer.…”
Section: Lbnl-59023mentioning
confidence: 99%